Legal Gender Equality as a Catalyst for Convergence - Sever, Can (IMF Working Papers; Working Paper ;, 2022)
The unequal treatment of women in the law is one of the most visible forms of gender inequality. Prevalent legal constraints on the basis of gender prevent women, and thereby economies, from reaching their true potential. In this regard, this paper (i) documents the evolution of gender discriminatory laws around the globe, and (ii) sheds light on the role of legal gender equality in income convergence across countries. It shows that despite the remarkable progress toward gender equality in the law over the last five decades, the legal environment across the world is still far from providing a level playing field for women. Moreover, cross-country gaps in gender discriminatory laws have persisted and even widened over the years, meaning that some countries have lagged behind the progress in repealing the laws that act as a barrier to women's economic inclusion. Based on a global sample since the 1970s, this paper finds that greater gender equality in the law facilitates cross-country income convergence over time. The results call for action and provide a reason to be optimistic going forward. They imply that legal reforms supportive of gender equality, which could indeed be actionable in the shorter term, help poorer countries catch up with the living standards in the advanced economies. These offer a window of opportunity in the post-Covid-19 period, given the adverse effects of the pandemic on economic growth and gender gaps.